Building useful evidence: changing the clinical research paradigm to account for comparative effectiveness research. (May 2012) - Greenfield, Sheldon; Kaplan, Sherrie H
Comparative effectiveness research (CER) calls for substantial changes in the way clinical research is conducted, interpreted and practically applied in the USA, in order to produce useful clinical evidence. Departing from classic efficacy and effectiveness research, the evolving CER paradigm requires structural and substantive innovations that address three basic questions: what works? for whom? and in whose hands? Addressing these questions will require fundamental changes in the approach to clinical research that include: the use of active treatments (or comparators) versus placebos in the comparisons of treatments, innovative or 'alternative' research methods, the specification and a priori design of studies to account for important subgroups, accounting for the nested nature of healthcare delivery in design and analysis of CER, the simultaneous study of multiple treatments or treatment modalities, the study of multiple outcomes (benefits and harms) for each treatment compared, and the reassessment of the value of different study designs in the hierarchy of collective 'evidence'. In order to aid individual providers and patients in making informed, personalized treatment decisions, guided by the best evidence possible, CER studies must generalize to a broad range of subgroups reflecting the spectrum of patients, providers and health systems that populate real-world practice settings. Without expansion in the scope, conduct and subsequent interpretation of clinical research reflected in the issues outlined above, CER will fall short of its potential for informing evidence-based practice and personalized medicine. The current paradigm for conducting, interpreting and applying clinical research does not meet the needs of optimal generalizability and application to individual physician–patient efforts to identify the most effective treatment, and therefore does not support the basic requirements of CER. The proposed changes should neither require decades nor exorbitant budgets to achieve. Using two examples, prostate cancer, and comparisons of single medications, we illustrated how the proposed changes in clinical research, matching strategy to each application, might be addressed.